The mediating effect of job involvement in the relationship between tennis Instructors' perceived organizational justice and turnover intentions: a multi-group analysis across generations - Sujin Kim; Jongho Kim (Frontiers Media S.A., 2024)
IntroductionThis study aimed to analyze the role of job involvement as a mediator in the relationship between tennis coaches' perceived organizational justice and their intention to leave, considering the unique professional context and demands of tennis coaching. Additionally, it sought to identify any generational differences in this model. The research categorizes perceived organizational justice into procedural and distributive justice, and job involvement into job attachment and job commitment.MethodsThe study incorporated data from 201 coaches working at commercial tennis facilities nationwide. Perceived organizational justice and job involvement were measured using validated scales. The mediation model was tested using structural equation modeling (SEM), and a multi-group analysis was conducted to identify generational differences.ResultsResults indicated that job involvement partially mediated the relationship between perceived organizational justice and turnover intentions, with distributive justice having a stronger total effect. The multi-group analysis revealed generational variances: distributive justice influenced turnover intentions more among the MZ generation, while procedural justice had a greater impact on the older generation.DiscussionThese findings offer valuable insights for commercial tennis facilities aiming to reduce turnover and manage generational conflicts. Understanding the differential impacts of procedural and distributive justice on various generations can help tailor strategies to enhance organizational operation and employee retention.ConclusionThe study highlights the importance of perceived organizational justice and job involvement in influencing tennis coaches' turnover intentions. The generational differences observed suggest that targeted interventions based on generational characteristics can be effective in reducing turnover and improving organizational stability. Future research should explore other potential mediators and extend the model to different sports and organizational contexts.